An Assistance of Building Children Character through Social Education Poster at Karyamukti Village - Aisyah Khumairo; Pepsa Anggriliana (CV. Creative Tugu Pena, 2022)
The character was a very important aspect in assessing the quality of human resources and becomes the basic foundation in developing social skills in the future. This article aimed to give an assistance of building the children character through media social of education posters at Karyamukti Village, Sekampung District, East Lampung Regency. One of the media that can be used to improve the children development was visualization media. The researchers used Asset Based Community Development (ABCD) that utilize the potential asset of students at community. The subject was 20 children at Karyamukti Village. Four stages activities in analyzing program involved preparing program, arrange the program, describing material, and evaluation program. The result showed that the implementation of this activity was effectively and received a large enough participation from the children and the benefits either form children and parents. The successful activities can be seen from the enthusiasm and following of the children to build their own character in participating in this educational poster activity Keywords: Children Character, Social Education Poster, Building Children Character